IMPLEMENTATION ANALYSIS OF THE MICRO WAQF BANK FINANCING AND MENTORING PROGRAM IN INDONESIA - Heriyati Chrisna; Yenni Samri Juliati Nasution (Proceeding International Seminar of Islamic Studies, 2022)
Community economic empowerment must be supported by empowerment, engineering, and conditioning strategies into tools to empower the people's economy, especially around pesantren. This article aims to analyze the implementation of financing programs and assistance to customers from Micro Waqf Bank in several regions in Indonesia. The method used is a library study by searching, reading, and reviewing research reports and library materials that contain the theories relevant to the research conducted. From the results of the study, it was found that almost all Micro Waqf Banks have carried out the financing and assistance process in accordance with the POJK, only there are still obstacles faced in the field, so that they still need solutions to parties related to the Micro Waqh Bank, OJK, Laznas and PinbukKeywords: Implementation, Financing, Mentoring,